Development of HOTS-Based Evaluation Instruments in Indonesian Language Lessons for Class V SD Negeri 60 Tondon - Dedi Setiawan; Munirah Munirah; Erwin Akib (Universitas Muhammadiyah Enrekang, 2022)
Development of HOTS-Based Evaluation Instruments in Indonesian Language Lessons for Class V Students at SD Negeri 60 Tondon. Supervised by Munirah and Erwin Akib. This study aims to determine the validity, practicality and effectiveness of developing HOTS-based evaluation instruments to determine student learning outcomes. This research is research and development, the development design using 4-D model. The subjects in this study were fifth grade students of SD Negeri 60 Tondon. Instruments Data collection was carried out through validation test sheets, teacher response questionnaires, student response questionnaires, HOTS instruments. The data analysis technique used is descriptive data analysis. The results showed that the HOTS-based evaluation instrument in the form of developing a HOTS-based evaluation instrument was at a value of 3.6 (91%) with a very valid category. The HOTS-based evaluation instrument was declared practical, the results of the analysis of the teacher's response with a value of 4 (100%) in the very practical category, and the results of the student responses with a value of 4 (100%) in the very practical category. The HOTS-based evaluation instrument was declared effective because in terms of student learning outcomes it achieved 81% completeness in the very good category so that it was declared effective. Students are active in the learning process by increasing the level of effective thinking reflected in good learning outcomes.